The performance assessment of reverse osmosis stations at Al-Mahalabea area - Ahmed, Mohammed F. (Scientific Review Engineering and Environmental Sciences (SREES), 2020)
The present study assesses RO stations at four sites in Al-Mahalabea area – Nineveh governorate, Iraq during the summer of 2013. The performance of RO stations are ranked by two methods: the Simple Additive Weight (SAW) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). Two groups of samples were collected from feed and permeate water for two periods (at zero time of operation and after ten weeks of operation) with eleven parameters for each sample were analysed. The highest overall rejection R efficiency appeared with the first set of parameters more than 90% (SO4, TDS, NO3, TH, and turbidity), while the second set was the least (Cl, Na, and total alkalinity – TA) ranged between 65 and 85%. It is observed that both the SAW and the TOPSIS methods are accurate to predict the performance efficiency.